2021
DOI: 10.21014/acta_imeko.v10i1.853
|View full text |Cite
|
Sign up to set email alerts
|

Fault detection and diagnosis of historical vehicle engines using acoustic emission techniques

Abstract: <span lang="EN-GB">The reactivation of artefact mechanisms is always a challenge for conservators. Non-invasive diagnostic techniques, applicable directly on the artifacts, allows for performing early-stage diagnostics and avoiding damage. The Acoustic Emission Monitoring of Historical Vehicles (ACUME_HV) project represents the first use of acoustic emission (AE) as a non-invasive technique for the diagnostics of historical vehicles. The aim of this project is to develop an objective, human-independent m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…In this paper, we investigate the use of data analysis techniques for the visualization and classification of the engine health status using data-driven solutions such as supervised machine learning. The paper focuses on the analysis of vibro-acoustic signals for the characterization of engines in different conditions (data presented in previous publications [17][18][19][20][21]). Research questions studied in this article focus on the use of AE signals and machine learning, and can be summarized as: 1) identify the engine that produces the signal; 2) determine if an engine has an anomaly; 3) determine which engine a record belongs to and if it has an anomaly.…”
Section: Goal and Research Questionsmentioning
confidence: 99%
See 4 more Smart Citations
“…In this paper, we investigate the use of data analysis techniques for the visualization and classification of the engine health status using data-driven solutions such as supervised machine learning. The paper focuses on the analysis of vibro-acoustic signals for the characterization of engines in different conditions (data presented in previous publications [17][18][19][20][21]). Research questions studied in this article focus on the use of AE signals and machine learning, and can be summarized as: 1) identify the engine that produces the signal; 2) determine if an engine has an anomaly; 3) determine which engine a record belongs to and if it has an anomaly.…”
Section: Goal and Research Questionsmentioning
confidence: 99%
“…The developed methodology and the results of the ACUME_HV project have been previously published in different journals and conference proceedings [17][18][19][20][21]. The ACUME_HV project showed that acoustic emission can be used to establish the state of preservation of historical engines before their reactivation and to detect the most common faults [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations